INTERLOCK KNITWEAR WOVEN FROM SPUN COTTON-NITRON YARN RESEARCH OF PHYSICAL AND MECHANICAL PROPERTIES OF TISSUES (Conferencea, 2023)
In this article, for the purpose of effective use of local raw materials, research works on the physical and mechanical properties of interlock fabric from spun cotton-nitron thread conducted.